Isolation of blood-brain barrier-crossing antibodies from a phage display library by competitive elution and their ability to penetrate the central nervous system. Issue 2 (17th February 2018) - Thom, George; Hatcher, Jon; Hearn, Arron; Paterson, Judy; Rodrigo, Natalia; Beljean, Arthur; Gurrell, Ian; Webster, Carl
ABSTRACT: The blood-brain barrier (BBB) is a formidable obstacle for delivery of biologic therapeutics to central nervous system (CNS) targets. Whilst the BBB prevents passage of the vast majority of molecules, it also selectively transports a wide variety of molecules required to maintain brain homeostasis. Receptor-mediated transcytosis is one example of a macromolecule transport system that is employed by cells of the BBB to supply essential proteins to the brain and which can be utilized to deliver biologic payloads, such as antibodies, across the BBB. In this study, we performed phage display selections on the mouse brain endothelial cell line, bEND.3, to enrich for antibody single-chain variable fragments (scFvs) that could compete for binding with a known BBB-crossing antibody fragment, FC5. A number of these scFvs were converted to IgGs and characterized for their ability to bind to mouse, rat and human brain endothelial cells, and subsequent ability to transport across the BBB. We demonstrated that these newly identified BBB-targeting IgGs had increased brain exposure when delivered peripherally in mice and were also able to transport a biologically active molecule, interleukin-1 receptor antagonist (IL-1RA), into the CNS. The antagonism of the interleukin-1 system within the CNS can result in the relief of neuropathic pain. We demonstrated that the BBB-targeting IgGs were able to elicit an analgesic response in a mouse model of nerve ligation-induced hypersensitivity when fused to IL-1RA.